Studies on the Antibacterial Activity of 3, 5-Diaryl Isoxazolines and 3,5-Diaryl Isoxazoles - V.B. Tayde, Miss; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some 3,5-diaryl isoxazolines and 3,5-diaryl isoxazoles were synthesizedby a novel method. These compounds have already beencharacterised by spectral data. They were screened for their antibacterialactivity against gram-positive and gram-negative bacteria.